Extensive Reading Instruction Via E-Books Impact On EFL Students’ Reading Attitude and Motivation, and Reading Skills - Radia Bouguebs (The Journal of Studies in Language, Culture and Society)
Extensive reading instruction that emphasizes quantity of books read gives priority to the student to choose the reading material. Opting for the one that fits their level of proficiency and interest makes EFL readers confront the phenomenon of e-books accessibility against paper books shortage. This research seeks to explore EFL students’ motivation and attitude towards e-books reading, and identify if this latter have the same impact on their reading skills as paper books.  In particular, the study aims at checking EFL students’ perceptions towards their experience in reading e-books and finding out if this kind of reading materials motivate them to read more as these latter improve their reading skills mainly comprehension and vocabulary acquisition. This work is led through the analysis of questionnaires administered to second year students of English at the École Normale Supérieure de Constantine as being subjects to extensive reading instruction training in their Reading Techniques sessions. Discussion of the results revealed that despite students’ definite preference for paper book; however, the numerous advantages offered by e-books as enlarging students’ culture and knowledge, vocabulary acquisition do stimulate EFL learners to cope with this new type of reading materials: e-books.